Kontekstualisasi Ayat Nut{Fah Dalam Al-Qur’an Dan Relevansinya Dengan Penentuan Jenis Kelamin (Kajian Tafsir An-Nu - Putra, Luthfi Abadi; Ghozali, Abdul Malik; Hendro, Beko (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2024)
This article aims to examine the interpretation of nutfah verses related to the process of human creation and gender determination, and uses the book of tafsir An-Nur by Teungku Muhammad Hasbi Ash-Shiddieqy and the Ministry of Religion's book of tafsir ilmi as a tool for interpreting nutfah verses. In this research The researcher analyzes by connecting the interpretation of the nutfah verses with the scientific approach of human genetics. The approach in this research uses qualitative methods guided by literature data, with a focus on content analysis. The results of this study found that the Qur'an answers issues related to sex determination, according to tafsir An-Nur and tafsir ilmi Kemenag indicating that men through nutfah (sperm) determine sex, this is supported by the scientific approach of human genetics, supported by the scientific approach of human genetics.